PENGARUH USIA TERHADAP JUMLAH SARAF NITRERJIK DI HIPOKAMPUS TIKUS - , REVINDA MONICA HARDIMAN, drh. Dwi Liliek Kusindarta, MP., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Aging was a defintite process in all individu. This proses consist of 3 juvenile, adult, and old phase. Juvenile was faster in mimic or memorize something new. This capability was called cognitive capability, which is regulated by the hipocampus. Hipocapus its self consist of 3 area, girus dentatus, hipocampus proper, and subiculum. One of the indication of increased cognitive capability could be seen from neurotransmitter distribution in hipocampus, one of the most important neurotransmitter was Nitric Oxide (NO). Aim of this research is to observe the effect of age towards amount of nitric oxide in nitrerjik nerve of rats brain. Nine male rats (Rattus norvegicus), 3, 8, and 12 weeks old from Gandok, Depok Sleman was used in this research. Rats were anaesthetized (ketamine 0,4-0,8 ml/kg and xylazine 10 mg/kg), perfused intracardialy with NaCl 0,9% continued with formalin 10% in phosphat buffer saline. The brain was taked out and processed for cryostat section 20 um thickness, stainned with hematoxylin eosin and NADPH diaphorase methode, examined with light microscope. The nitrergic nerve cells body were count and reported descriptively. Nitrergic nerve cells body were found in three areas of hippocampus, dentatus gyrus, hippocmapus proper, and subiculum. Nerve cells were oval, circuler, and piramidal in shaped. The number of nitrergic nerve cells body in cornue amunis 3, dentatus gyrus, and subiculum waere increased related with age of rats and the highest in dentatus gyrus..